Utilization of intensive behavioural treatment for obesity in patients with diabetes. Issue 1 (4th November 2020) - Kraschnewski, Jennifer; Yeh, Hsin‐Chieh; Francis, Erica; Kong, Lan; Lehman, Erik; Rovito, Stephanie; Poger, Jennifer; Bryce, Cindy
Summary: Obesity is a leading public health concern. The Centers for Medicare and Medicaid Services implemented a healthcare procedure code for intensive behavioural therapy (IBT) in 2012 to facilitate payment for addressing obesity in primary care settings, followed by universal coverage by insurers for all adults. Our objective was to understand utilization of IBT from 2009 to 2017 in patients with a diabetes diagnosis. Leveraging electronic health record data from the PaTH Clinical Data Research Network (CDRN), a partnership of six health systems, utilization of IBT was summarized at a yearly basis. The trend of IBT prevalence was examined for patients with diabetes by gender, race, age (>=65 vs <65) and rurality. A total of 205, 913 patients were included. While utilization of IBT is low (0.24% in 2017), use of IBT increased among patients with commercial insurance and Medicaid (codes S9449 and S9470) in 2011, and among patients with Medicare (code G0447) in 2012. IBT users tended to be less than 65 years of age, female, non‐White (Black or Hispanic), and reside in urban areas. Overall, use of IBT in patients with diabetes remains low. Future work is necessary to understand the impact of IBT and, if effective, how to increase use within primary care.